Association between splenic volume and pulsatility index in patients with left ventricular assist devices. Issue 4 (April 2021) - Hiraiwa, Hiroaki; Okumura, Takahiro; Sawamura, Akinori; Kondo, Toru; Kazama, Shingo; Kimura, Yuki; Shibata, Naoki; Arao, Yoshihito; Oishi, Hideo; Kato, Hiroo; Kuwayama, Tasuku; Yamaguchi, Shogo; et al.
The spleen serves as a blood volume reservoir for systemic volume regulation in heart failure (HF) patients. Changes are seen in spleen size in advanced HF patients after left ventricular assist device (LVAD) implantation. The pulsatility index (PI) is an indicator of native heart contractility with hemodynamic changes in patients using LVAD. We hypothesized that the splenic volume was associated with the PI, reflecting the hemodynamics in advanced HF patients with LVADs. Herein, we investigated the relationship between splenic volume and PI in these patients. Forty-four patients with advanced HF underwent implantation of HeartMate II ® (Abbott, Chicago, IL, USA) as a bridge to heart transplantation at the Nagoya University Hospital between October 2013 and June 2019. The data of 27 patients (21 men, median age 46 years) were analyzed retrospectively. All patients underwent blood tests, echocardiography, right heart catheterization, and computed tomography (CT). Spleen size was measured via CT volumetry; the splenic volume (median: 190 mL) correlated with right arterial pressure ( r  = 0.431, p  = 0.025) and pulmonary capillary wedge pressure ( r  = 0.384, p  = 0.048). On multivariate linear regression analysis, the heart rate (β = −0.452, p  = 0.003), pump power (β = −0.325, p  = 0.023), and splenic volume (β = 0.299, p  = 0.038) were independent determinants of PI. The splenic volume was associated with PI, reflecting the cardiac preload in advanced HF patients with LVADs. Thus, spleen measurement using CT may help estimate the systemic volume status and understand the hemodynamic conditions in LVAD patients.